Check-list of the genus Cortodera mulsant, 1863 (Coleoptera: Cerambycidae) in Turkey with two new records - Özdikmen, Hüseyin (Acta entomologica slovenica (Ljubljana), 2003)
The present list is the first attempt to register all modern Cortodera taxa of the whole territory of Turkey. Complete list of Turkish (European Turkey and Anatolia) Cortodera is given. It includes 20 species and 25 taxa of the species group (with subspecies); species introduced and established in Turkey are also included. Nominate subspecies are not mentioned, if other subspecies do not occur in Turkey. Main and important (but not all) synonyms, as well as taxonomic and geographical notes are also given.
Keywords: Coleoptera; entomologija; hrošči; Turčija; Turkey